Associations between metabolic dysfunction–associated steatotic liver disease and physical and mental health–related quality of life in older adults - Marzieh Nasr Azadani; Mojtaba Lotfaliany; Najmeh Davoodian; Michael Berk; Robyn L. Woods; Joanne Ryan; John J. McNeil; Julie A. Pasco; Nigel Stocks; Stuart K. Roberts; William Kemp; Ammar Majeed; et al. (GeroScience, 2026)

Assessment of Fellowship Didactic Curricula in Hematology/Oncology: Cross-Sectional Findings From the PODCAST-HOF Trial - Ronak H. Mistry; Karine Tawagi; Daniel J. Hausrath; Samantha A. Armstrong; Inas A. Abuali; Ankoor N. Biswas; Srijan Valasapalli; Pranali S. Pachika; Moriah K. Forster; Ericson Stoen; Yurhee Lee; Giuliana G. Berardi; et al. (Journal of Cancer Education, 2026)

Test of Rapamycin in Aging Dogs (TRIAD): study design and rationale for a prospective, parallel-group, double-masked, randomized, placebo-controlled, multicenter trial of rapamycin in healthy middle-aged dogs from the Dog Aging Project - Amanda E. Coleman; Kate E. Creevy; Rozalyn Anderson; May J. Reed; Virginia R. Fajt; Kathleen M. Aicher; Genna Atiee; Brian G. Barnett; Ryan D. Baumwart; Beth Boudreau; Suzanne M. Cunningham; Matthew D. Dunbar; et al. (GeroScience, 2025)

Strengths and limitations of the worm development and activity test (wDAT) as a chemical screening tool for developmental hazards - Piper Reid Hunt; Bonnie Welch; Jessica Camacho; Joelle K. Salazar; Megan L. Fay; Jon Hamm; Patricia Ceger; Dave Allen; Suzanne C. Fitzpatrick; Jeffrey Yourick; Robert L. Sprando (Toxicology and Applied Pharmacology, 2024)

Identifying priority sites for whale shark ship collision management globally - Freya C. Womersley; Christoph A. Rohner; Kátya Abrantes; Pedro Afonso; Shin Arunrugstichai; Steffen S. Bach; Shir Bar; Adi Barash; Peter Barnes; Adam Barnett; Ginevra Boldrocchi; Noemie Buffat; et al. (Science of The Total Environment, 2024)

Population origin and heritable effects mediate road salt toxicity and thermal stress in an amphibian - Lauren M. Conner; Debora Goedert; Sarah W. Fitzpatrick; Amber Fearnley; Emma L. Gallagher; Jessica D. Peterman; Mia E. Forgione; Sophia Kokosinska; Malik Hamilton; Lydia A. Masala; Neil Merola; Hennesy Rico; et al. (Chemosphere, 2024)

The companion dog as a model for inflammaging: a cross-sectional pilot study - Sarah M. Schmid; Jessica M. Hoffman; Jena Prescott; Holley Ernst; Daniel E. L. Promislow; Joshua M. Akey; Brooke Benton; Elhanan Borenstein; Marta G. Castelhano; Amanda E. Coleman; Kate E. Creevy; Kyle Crowder; et al. (GeroScience, 2024)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Sperm maturation and male tactic‐specific differences in ejaculates in the plainfin midshipman fish Porichthys notatus - Jessica S. Miller; Aneesh P.H. Bose; John L. Fitzpatrick; Sigal Balshine (Journal of Fish Biology, 2019)
Using the plainfin midshipman fish Porichthys notatus , a species with alternative reproductive tactics (ARTs), we investigated how sperm maturation shapes sperm competitive abilities. We compared sperm performance and morphology before and after final sperm maturation by sampling sperm from the testes and stripped ejaculates of guarders and sneakers. In accordance with sperm competition risk theory, ejaculates from sneaker males had three times as much sperm as ejaculates from guarder males and sneaker males produced faster swimming sperm than guarder males, but this was only the case after final sperm maturation had occurred. Additionally, fully mature sperm found in ejaculates had larger heads and midpieces than sperm found in the testes. These results emphasize the important role played by non‐sperm components of an ejaculate in mediating sperm performance and potentially also morphology.

Functioning of Coastal River-Dominated Ecosystems and Implications for Oil Spill Response: From Observations to Mechanisms and Models - Adam Greer; Alan Shiller; Eileen Hofmann; Jerry Wiggert; Sally Warner; Sabrina Parra; Chudong Pan; Jeffrey Book; DongJoo Joung; Steven Dykstra; Jeffrey Krause; Brian Dzwonkowski; et al. (Oceanography, 2018)

How will climate novelty influence ecological forecasts? Using the Quaternary to assess future reliability - Matthew C. Fitzpatrick; Jessica L. Blois; John W. Williams; Diego Nieto‐Lugilde; Kaitlin C. Maguire; David J. Lorenz (Global Change Biology, 2018)
Future climates are projected to be highly novel relative to recent climates. Climate novelty challenges models that correlate ecological patterns to climate variables and then use these relationships to forecast ecological responses to future climate change. Here, we quantify the magnitude and ecological significance of future climate novelty by comparing it to novel climates over the past 21,000 years in North America. We then use relationships between model performance and climate novelty derived from the fossil pollen record from eastern North America to estimate the expected decrease in predictive skill of ecological forecasting models as future climate novelty increases. We show that, in the high emissions scenario (RCP 8.5) and by late 21st century, future climate novelty is similar to or higher than peak levels of climate novelty over the last 21,000 years. The accuracy of ecological forecasting models is projected to decline steadily over the coming decades in response to increasing climate novelty, although models that incorporate co‐occurrences among species may retain somewhat higher predictive skill. In addition to quantifying future climate novelty in the context of late Quaternary climate change, this work underscores the challenges of making reliable forecasts to an increasingly novel future, while highlighting the need to assess potential avenues for improvement, such as increased reliance on geological analogs for future novel climates and improving existing models by pooling data through time and incorporating assemblage‐level information.

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Intensified mollusk exploitation on Nevis (West Indies) reveals ~six centuries of sustainable exploitation - Aaron S. Poteate; Scott M. Fitzpatrick; Meagan Clark; Jessica H. Stone (Archaeological and Anthropological Sciences, 2015)

Close agreement between pollen‐based and forest inventory‐based models of vegetation turnover - Diego Nieto‐Lugilde; Kaitlin C. Maguire; Jessica L. Blois; John W. Williams; Matthew C. Fitzpatrick (Global Ecology and Biogeography, 2015)
Aim Fossil records are being increasingly used to help understand the consequences of climate change for biodiversity. Pollen records from the late Q uaternary are among the most commonly used fossil data, but pollen‐based inferences of biodiversity can potentially be confounded by spatial and taxonomic uncertainties and the influence of non‐climatic abiotic factors such as soils on vegetation–climate relationships. Using paired pollen and vegetation inventories, we assess the fidelity of pollen‐based estimates of compositional turnover of vegetation along environmental gradients given various sources of uncertainty. Location E astern U nited S tates. Methods We used modern pollen records and forest composition data from F orest I nventory and A nalysis ( FIA ) plots to fit generalized dissimilarity models. To address how uncertainties in pollen records affect estimates of turnover, we coarsened the vegetation data spatially from individual plots to 10‐ and 30‐arcmin resolution and taxonomically from species to genus. To determine whether soil properties influenced turnover, we used deviance partitioning between models including climate or soil variables versus models with a combination of both. Results Pollen‐based estimates of turnover were highly correlated with those based on FIA data, but tended to be lower, mainly due to differences in taxonomic resolution and secondarily to differences in spatial resolution. Neither spatial nor taxonomic uncertainty substantially reduced the correlation between pollen‐ and FIA ‐based estimates of turnover. FIA data best matched pollen records when they were aggregated to genus and 30‐arcmin resolution. Vegetation–climate relationships were similar across datasets, although models sometimes differed. The influence of soil variables was negligible compared with climate variables and did not improve model fit. Pollen thresholds did not greatly affect the form and strength of pollen–vegetation relationships. Main conclusions Pollen can act as a robust proxy for vegetation turnover, thereby supporting the use of pollen‐based estimates of turnover to predict temporal changes in vegetation.